The impact of shame and self-judgment on psychopathology in infertile patients - Galhardo, Ana (2013)
Background: Little is known about psychological processes of infertile couples pursuing medical treatment in comparison with fertile couples and adoption candidates who also suffer from infertility but are not seeking medical help. This study aims to contribute to a better understanding of these individuals in terms of psychological processes (such as external shame, internal shame and self-judgment) and their association with psychopathology, also attending to gender differences. Methods: One hundred control couples without known fertility problems [fertile group (FG)], 100 couples with an infertility diagnosis and pursuing medical treatment [infertile group (IG)], and 40 couples with an infertility diagnosis who are applying for adoption [adoption group (AG)] completed the instruments: Beck Depression Inventory, Spielberger State-Trait Anxiety Inventory, Others as Shamer, Experience of Shame Scale and the Self-compassion Scale. One-way analysis of variances were used to compare the three groups demographic and study variables. Pearson correlations and linear multiple regression analysis were performed to investigate the associations between shame, self-judgment, depression and anxiety. To explore gender differences, T-tests were used. Results: The IG group scored higher than FG and AG in measures of depression, anxiety, external shame, internal shame and self-judgment. In infertile couples, self-judgment, external shame and internal shame emerged as significant predictors of depressive symptomatology. Women with an infertility diagnosis tend to present higher levels of depressive and anxiety symptoms in comparison with fertile controls and adoption candidates. Conclusions: This study highlights the importance of emotional regulation processes such as internal and external shame, and self- judgment, to the understanding of psychopathological symptomatology associated with infertility. Our results suggest that these issues should be addressed in a therapeutic context with these couples. Nevertheless, the heterogeneity of the infertile group, in what concerns different stages of medical diagnosis and treatment, might represent a limitation in the interpretation of our findings.